Prerequisites for Calendar Ritualism Integration to the Process of Spiritual Development of Students of Modern School of Mountain Regions - Lappo, Violetta (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The profit of involving calendar holidays in the process of school children bringing up is proved in the article. The author confirms that there are many good customs and rituals with deep bringing up content. Ethnic Hutsul traditions had symbolic meaning and contributed their moral bringing up. The number of examples about children's upbringing in Hutsul families is given here, which helps in training them to religious and secular traditions. It is also said about holiday rituals, where small Hutsul children were involved. A lot of Hutsul customs and rituals have already been forgotten. But the author appeals to their renascence. The author is sure of it because customs and rituals form upbringing tradition, which proved its effectiveness during many centuries. Partly, it is important to meet children to new traditions of modern mountain schools of Hutsulshchyna (Hutsulland) to form true valuable orientation. Only this is the basis of the personality spiritual world. The author proposes to reveal the celebrations of ancient traditions such holidays as: Christmas, Easter, Trinity. During these holidays Hutsul people tried to do a lot of charity things, helping sick people, visiting ill, and making mention of the departed. That's why it is important that the modern pupils of mountain schools not only new, but followed public calendar traditions. It has to be not only following certain ritual actions, but it has to be the ability to the spiritual perception of Hutsul cultural heritage.